Rola satysfakcji z pracy oraz przywiązania do organizacji dla zamiaru jej opuszczenia. Weryfikacja modelu - Wnuk, Marcin (Humaniora. Czasopismo Internetowe, 2021)
The aim of the study was verified job satisfaction mediating role between organizational commitment and intention to quit the organization. Additionally checked if job satisfaction and organizational commitment mediate between salary satisfaction and intention to quit the organization. Subjects were 484 employees from one IT organization. According to results job satisfaction partially mediated between affective commitment and intention to quit the organization as well as totally mediated between normative commitment and intention to quit. Additionally job satisfaction, affective commitment as well as continuance commitment partially mediated between salary satisfaction and intention to quit the organization.